Sex and stroke in thrombolyzed patients and controls - Hametner, Christian; Kellert, Lars; Ringleb, Peter A. (Stroke, 2017)
Background and Purpose—We hypothesized that any sex-related difference in outcome poststroke is explained by other prognostic factors and that the response to intravenous recombinant tissue-type plasminogen activator (r-tPA) is equal in males and females after adjustment for such factors. Methods—We accessed an independent collection of randomized clinical trials—the VISTA (Virtual International Stroke Trials Archive). Data were preprocessed by selecting complete cases (n=8028) and matching females to males (coarsened exact matching, n=4575, 24.3% r-tPA). Outcome was assessed by the 7-point modified Rankin Scale (mRS) measured at 90 days after ischemic stroke. Relationship among variables was estimated by adjusted regression analysis. Results—In nonthrombolyzed patients, ordinal analysis of mRS adjusting for stroke- and sex-related prognostic factors suggested comparable outcomes for females and males (odds ratio, 0.96; 95% confidence interval, 0.85-1.06). Females responded comparably to r-tPA as did males, irrespective of the outcome definition of mRS (ordinal: PInteraction=0.46, relative excess risk because of interaction=0). The number needed to treat was 6.8 and 11.2 for 1 female to achieve mRS score of 0 to 2 and 0 to 1, which was highly congruent with males. Analysis for a nonlinear variation of age-by-sex revealed a good outcome for females <45 years with significant disadvantage thereafter (mRS score of 0-2: PInteraction=0.004). No relationship between sex, r-tPA, and bleeding complications was evident. Conclusions—Functional outcome (mRS) without r-tPA was overall similar between the sexes, as was the response to r-tPA. Nonlinear sex-by-age interaction improved estimates of functional independence; this should be considered in sex-related studies in stroke.